Ukraine Dairy Market: State and Prospects of Development - Pronko, Lyudmila; Kolesnik, Tatyana; Samborska, Oksana (European Journal of Sustainable Development, 2020)
The article discusses topical issues regarding the prospects for the development of the milk and dairy market. It is investigated that the largest breakthrough has been achieved by the dairy industry with milk, since DSTU 3662: 2018 "Cow’s milk" came into force on January 1, 2019, the inflow of milk processing plants is not lower than the first grade, and it is known that private households provide largely only milk of the second grade. As a result, the quality and safety of milk purchased from industrial farms has increased significantly. The authors emphasize that an important factor in the development of production activity for producers is the selling price of milk, which in 2018 in Ukraine amounted to 7602,4 UAH /t, which is 368,4 UAH /t more than in 2014.It is substantiated that there are a number of problems in the dairy industry of Ukraine that hinder its further development, the main ones being: increased competition from illegally operating enterprises, the shadow market, counterfeit products, lack of confidence and lack of cooperation between producers and processors of products, etc. The author has proved that these problems can be solved by combining milk producers and processors in cooperatives and providing them with effective state support. Keywords: milk, dairy industry, quality, livestock, dairy cattle, selling price, market.